2018
DOI: 10.3389/fmicb.2018.01301
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Novel Polyamine Scaffold With Potent Efflux Pump Inhibition Activity Toward Multi-Drug Resistant Bacterial Pathogens

Abstract: We have previously reported the use of combinatorial chemistry to identify broad-spectrum antibacterial agents. Herein, we extend our analysis of this technology toward the discovery of anti-resistance molecules, focusing on efflux pump inhibitors. Using high-throughput screening against multi-drug resistant Pseudomonas aeruginosa, we identified a polyamine scaffold that demonstrated strong efflux pump inhibition without possessing antibacterial effects. We determined that these molecules were most effective w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 80 publications
(130 reference statements)
1
35
0
Order By: Relevance
“…Using HTS, Fleeman et al [67] identified five different polyamine derivatives, consisting of a core scaffold (Figure 7) with EPI activity in P. aeruginosa, A. baumannii and S. aureus. The inhibitory activity of the compounds was determined using EtBr accumulation assays in strains displaying varying level of efflux expression.…”
Section: Epis and Their Potential Role In Biofilm Disruption In P Aementioning
confidence: 99%
“…Using HTS, Fleeman et al [67] identified five different polyamine derivatives, consisting of a core scaffold (Figure 7) with EPI activity in P. aeruginosa, A. baumannii and S. aureus. The inhibitory activity of the compounds was determined using EtBr accumulation assays in strains displaying varying level of efflux expression.…”
Section: Epis and Their Potential Role In Biofilm Disruption In P Aementioning
confidence: 99%
“…Our results showed that niosome‐encapsulated tobramycin could reduce the EtBr MIC value by two to four times which is indicating the efflux pump inhibitory of niosome encapsulated tobramycin. Efflux pump systems in P. aeruginosa strains expel antimicrobial agents out the cells, contribute to the intrinsic resistance of bacteria 57,58 . Moreover, biofilm formation reduces the efficacy of antimicrobial agents and several studies showed the relationship between biofilm formation and antibiotic resistance 59 .…”
Section: Discussionmentioning
confidence: 99%
“…This result is encouraging because cytotoxicity is one of the major drawbacks to the clinical use of putative EPIs. For example, NMP and PAβN are toxic because of their serotonin agonist properties [41] and membrane depolarizing activity [42], respectively.…”
Section: Discussionmentioning
confidence: 99%